Analysis of the influence of temperature and hold time in the solid carburization process on the hardness and microstructure of AISI 1020 and 1045 using Oil Cooling - Safriwardy, Ferri; Rizki, Muhammad Nuzan; Masrullita, M; Daniel, Muhammad (Universitas Malikussaleh, 2023)
This study aims to determine the effect of variations in temperature and holding time on the value of hardness and microstructure in the carburizing process of low-carbon steel and medium-carbon steel. The temperature variations used during the carburizing process were 850oC and 950oC with variations of the holding time used being 15 minutes and 30 minutes. The types of materials used are AISI 1020 steel and AISI 1045 steel. In the carburizing process, the carbon source used is wood charcoal powder. After the process of adding carbon elements, the material will be quenched in the oil medium. The tests carried out were hardness testing and microstructure observations. The hardness test used the B-scale Rockwell hardness test method. The surface etching process of the material used a nital etching solution, namely a mixture of 3% nitric acid (HNO3) and 97% ethanol. The results showed that the lowest increase in hardness occurred at 850oC with a holding time of 15 minutes, namely 82.00 HRB for AISI 1020 steel and 95.66 HRB for AISI 1045 steel. Meanwhile, the highest increase in hardness occurred at a temperature of 950oC with a holding time of 30 minutes. namely 93.00 HRB on AISI 1020 steel and 105.33 HRB on AISI 1045 steel. This shows that the higher the temperature and the longer the holding time, the higher the hardness value.